Penerapan Panel Surya sebagai Sumber Energi Listrik Alternatif pada Gedung Fakultas Teknik Universitas Teuku Umar - T. M. Azis Pandria; Nissa Prasanti (Jurnal Serambi Engineering, 2021)
After turning into a state university, Universitas Teuku Umar continues to improve a number of infrastructures including the addition of a number of buildings. Currently the only source of electricity used to run all facilities in the building only from PLN, so that in the face of obstacles such as blackouts, suspension of electricity supply, or other technical constraints will result in the cessation of all activities so that it has an impact on the decline in the performance of the Faculty of Engineering in general. Research on the application of solar panels installed on the roof of the building (rooftop) as Building Applied Photovoltaic (BAPV) was conducted. The purpose of the study is to find out the number of solar panels and other devices needed for the application of PLTS in the Faculty of Engineering Building. PVsyst V7.2 software It is used to obtain daily solar radiation values at the locations reviewed. The existing Total Energy (TE) value calculation method is used to determine the capacity of solar panels and other supporting equipment. Results show an existing TE value of 20,422 Wh/day or equivalent to 20,422 kWh/day. Based on te value the number of solar panels needed as much as 33 units of capacity 120 Wp, Solar Charge Controller (PWM) 12 V-250 A 1 unit, VRLA Gel Battery Brand VOS 12V - 150 Ah 41 units, Inverter Pure Sine Wave (PSW) Split Phase Inverter Charger Series power 1-6 KW 1 unit.